Ocular Injuries After Bungee Jumping - Acharya, Keshav; Mahat, Birendra; Kandel, Himal (Journal of Nepal Health Research Council, 2024)
We present a case of ocular injuries post bungee jumping in Nepal. A 26 year old female presented to our clinic with bilateral Sub Conjunctival Hemorrhage (SCH) after bungee jumping. Her best corrected visual acuity was 20/20 in both eyes. No other intraocular hemorrhage was revealed in her dilated ocular examination. Conservative treatments with artificial tears were given to her and follow up visit after one week was advised. The SCH was resolved after a treatment of one week. Her visual acuity remained stable and no other ocular complications were found. To conclude, bungee jumping can be the cause of several ocular injuries. Further studies are required to identify the causes and potential risk factors. Keywords: Bungee jumping, ocular injury; sub conjunctival haemorrhage.